Effect of temperature and relative humidity on oviposition, survival and seed damage by Callosobruchus maculatus on different hosts and evaluation of pigeon pea (Cajanus cajan) cultivars for resistance - SINGH, DHRUV; BOOPATHI, T; SINGH, D V; GEETHANJALI, L (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2021–2023 at Sardar Vallabhbhai Patel University of Agriculture and Technology, Meerut, Uttar Pradesh, to investigate the influence of temperature and relative humidity on oviposition, adult survival, and seed damage caused by the pulse beetle, Callosobruchus maculatus (F.), in various pulse crops, and evaluated the resistance of selected pigeon pea [Cajanus cajan (L.) Millsp] cultivars. Experiments were conducted under three environmental conditions, viz. 20°C/80% RH, 30°C/70% RH, and 40°C/60% RH. The experiment was laid out in a completely randomized design (CRD) with four replications. Soybean (Glycine max) was identified as the most preferred host for oviposition, with egg deposition per seed reaching 4.17, 5.44, and 2.64 under the respective conditions. Pigeon pea supported the highest adult survival (22.34, 64.65 and 13.31%), whereas lentil exhibited the lowest oviposition and survival, indicating strong resistance. Seed damage was highest in pigeon pea (27.04–36.59%), followed by green gram and chickpea, while lentil remained largely unaffected. Further evaluation of 15 pigeon pea cultivars commonly grown in western Uttar Pradesh (India) revealed significant variation in susceptibility. Cultivar BWR-23 exhibited the lowest adult emergence (19.23%), indicating resistance, whereas BSMR-146 and BSMR-198 showed the highest oviposition rates (6.61 and 6.46 eggs per female, respectively). BSMR-198 recorded the highest seed damage, followed by WSA-1, BSMR-146, T-21, and Bahar. These results highlight the significant influence of environmental conditions on pest behaviour and demonstrate variability in resistance among pigeon pea varieties. The findings provide critical insights for breeding programs and support the development of integrated pest management strategies targeting C. maculatus.